Assessing the clinical applicability of prior head imaging in patients with chronic rhinosinusitis. Issue 1 (16th November 2017) - Bhalla, Vidur; McCann, Adam; Sykes, Kevin; Hoover, Larry; Beahm, D. David; Chiu, Alexander
Abstract : Background: Patients often have received some modality of head imaging prior to being evaluated for chronic sinonasal complaints, and the clinical significance of these scans on current sinonasal symptomatology is unknown. Methods: We performed a retrospective, cohort study of 578 patients with chronic sinonasal indications for maxillofacial computed tomography scans (CTs) in 2016. Patients were included if previous head cross‐sectional imaging had been performed. Lund‐McKay (LM) scores were calculated on the prior CT scan for each patient and compared to LM scores of the most recent scan. Scans with LM scores ≤3 were deemed normal, scores >3 were deemed positive, and Δ >3 was deemed a significant change. Results: Of 578 patients, 153 (26.5%) patients had previous imaging. Overall, a strong correlation was noted between scans ( r = 0.791, p < 0.001). Significant correlations remained with the subset of positive prior scans ( r = 0.743, p < 0.001). The 3 most common prior imaging modalities were maxillofacial CT, head CT, and brain magnetic resonance imaging (MRI). Correlations between these modalities and subsequent maxillofacial CTs range from strong to moderately strong. Women were significantly more likely to have negative prior imaging ( p = 0.048). Patients with negative prior imaging (80/153) were significantly more likely to remain unchanged (71/80) compared to patients with positive prior scans (56/73) ( p = 0.023). Conclusion: Prior head imaging highly correlates to future maxillofacial CT in patients with chronic sinonasal complaints, and patients with prior negative scans are likely to remain negative on future imaging. If prior head scans exist, practitioners may want to avoid ordering additional scans in the absence of changing symptoms.